2004
DOI: 10.1007/s11837-004-0231-2
|View full text |Cite
|
Sign up to set email alerts
|

Mass balance calculations in copper flash smelting by means of genetic algorithms

Abstract: This paper presents mass balance calculations using genetic algorithms for copper smelting in an Outokumpu fl ash furnace. Based on the elemental composition of the copper concentrates being fed to the reactor, the mineralogical composition of the concentrate mixture is adjusted by means of genetic algorithms. The macroscopic mass balance equations for the species entering and leaving the furnace are solved and the compositions and fl ow rates of matte, slag, and the off-gas stream are computed. Good agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Various studies have been performed on flash smelting furnaces with different objectives, including predicting furnace operating conditions in different situations, minimizing fuel consumption, reducing environmental pollutants, and studying the effect of concentrated particle size and their distribution combustion inside the furnace. In 2004, Sanchez-Corrales et al 3 performed mass balance calculations for an Outokumpu flash furnace using a genetic algorithm. Their research performed calculations for two different feed mixtures to the furnace and observed a good agreement between the modeling results and the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been performed on flash smelting furnaces with different objectives, including predicting furnace operating conditions in different situations, minimizing fuel consumption, reducing environmental pollutants, and studying the effect of concentrated particle size and their distribution combustion inside the furnace. In 2004, Sanchez-Corrales et al 3 performed mass balance calculations for an Outokumpu flash furnace using a genetic algorithm. Their research performed calculations for two different feed mixtures to the furnace and observed a good agreement between the modeling results and the experimental results.…”
Section: Introductionmentioning
confidence: 99%